STUDENTS’ READING ABILITY IN OPERATING COMPUTER PROGRAM (English Community Journal, 2022)
This research was conducted to know the students’ reading ability at computer program in Bina Insan University and to find out the good technique in teaching and learning process which appropriate for the students. The method was used in this research was descriptive qualitative research. There was 6 classes in computer program with 185 students as the population, and for the informant in this research was 12 students. From this research was found that most of the students still have some problems in teaching and learning process especially in reading comprehension, and comprehend the instruction when they operate the computer program. Students also fell that English is a scary subject because they just got t know English lessons when they were in Junior High School.